THE COGNITIVE STUDY OF NEUROLINGUISTIC ELEMENTS IN ENGLISH - Jurаyevа Muqаddаm Аbdug‘оfur qizi (Educational Research in Universal Sciences, 2023)
A crucial component of human communication is language. It is the most efficient form of communication and is regarded as a significant development for humans. The English language is vital to modern civilization and serves as a window to the rest of the globe. All around the world, English is becoming more and more in demand as a language of communication. Speaking proficiency is a crucial component of learning the English language. Learners typically experience lack of confidence, worry, nervousness, and apprehension when learning a new language. The process of learning to speak a language is greatly influenced by psychological variables. The purpose of this article, "Psychological Factors Affecting English Language Learning: The goal of a neurolinguistic perspective is to emphasize the significance of variables that influence language acquisition. One of the biggest challenges is the learner’s perception, which is dominated by psychological factors. The field of neurolinguistics studies the relationship between languages and the human mind. An approach to communication and personal development is neurolinguistic programming. It is also recognized as a superb way for teaching second languages because it helps students perform perfectly. By applying mental techniques like visualization, it brings forth the control of complex sensations and thoughts. It aids in enhancing learners’ mental states regarding their hesitancy. The perception of making mistakes, low self-esteem, and situational anxiety are psychological issues. The investigation’s goal is to determine some potential remedies that address the causes and consequences of NLP and assist language learners in overcoming their lack of confidence and fear when learning a language.